Evaluation of lean six sigma implementation in reducing patient waiting time in hospitals: A literature review - Assyifa Ramadhani; Nadia Putri Untiami; Reynanda Sabrina; Acim Heri Iswanto (PT WIM Solusi Prima, 2026)
The surge in National Health Insurance (JKN) participants to 267.3 million by the end of 2023 has significantly increased hospital operational workloads, leading to prolonged patient waiting times. Excessive waiting time reflects low process efficiency driven by non-value-added activities (waste). This issue severely diminishes patient satisfaction and contributes to global healthcare financial inefficiencies estimated at 20–40%. This study aims to synthesize empirical evidence regarding the effectiveness of DMAIC-based Lean Six Sigma (LSS) in reducing patient waiting times in hospitals, identify implementation challenges, and formulate strategic management recommendations. A systematic literature review was conducted by analyzing nine original research articles sourced from Google Scholar, PubMed, and PMC databases. Data were extracted based on methodology (DMAIC, VSM, pre-post trial), key findings, and field challenges, followed by a narrative synthesis. The synthesis demonstrates that LSS consistently and significantly reduces patient waiting times without requiring substantial capital investment. Primary barriers include Hospital Management Information System (SIMRS) instability, unergonomic facility layouts, manual prescribing practices, and slow adaptation to statistical competencies among staff. Effective improvement strategies focus on waste elimination, Lean tools application (5S, Kanban), and digitalizing administrative workflows. The implementation of DMAIC-based LSS proves to be an effective, measurable, and sustainable approach to reducing patient waiting times. Hospital management is highly recommended to integrate LSS as an internal quality regulation, enhance integrated IT infrastructure, and conduct periodic training on DMAIC methodologies for healthcare personnel.